Profil Muka Air Banjir 25 Tahun Di Sungai Siak Segmen Meranti Pandak Dengan HEC-RAS - Rakhmad Ramadhan; Bambang Sujatmoko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The area located on the banks of the Siak river, especially the Meranti Pandak Village area, is an area that has the potential for flooding and inundation during high rainfall and the influence of high tides on the Siak river. Floods that occurred in this area inundated several infrastructures such as roads and residential areas. Based on Kompas (2018), floods with a height of 60 cm – 1 m hit residents of RW 02 and RW 12, Meranti Pandak Village. The stages of the research carried out are by analyzing the frequency of rainfall data first, then calculating the planned discharge with HSS Nakayasu, then hydraulic modeling using the HEC-RAS Program, after the flood water level is obtained, the gate and water pump planning are carried out. Based on the results of the analysis of the flood height of the Siak river at the 25-year return period, the flood level in the upstream river, cross section 17 (SC 17) is 19,30 m or -0.90 m from the left bank of the river (non-flooded condition) and 0.30 m from the right bank of the river (flood condition) and the flood face elevation at the downstream (flood condition), cross section 1 (SC 1) is 17,35 m or 1.94 m from the left bank (flood condition) and 1.45 m from the right bank (flood condition).Keyword: flood, rainfall, HEC-RAS